Bis-(3-amino-2-pyridine) diselenide improves psychiatric disorders –atopic dermatitis comorbidity by regulating inflammatory and oxidative status in mice. (25th August 2021) - da Fonseca, Caren Aline Ramson; dos Reis, Angélica Schiavom; Pinz, Mikaela Peglow; Peglow, Thiago Jacobsen; Schumacher, Ricardo Frederico; Perin, Gelson; Martins, Amanda Weege da Silveira; Domingues, William Borges; Campos, Vinicius Farias; Soares, Mauro Pereira; Roehrs, Juliano Alex; Luchese, Cristiane; et al.
Abstract: Suppressive effect of bis (3-amino-2-pyridine) diselenide (BAPD) on psychiatric disorders – atopic dermatitis (AD) comorbidity in mice was investigated. To sensitize the animals, 2, 4-dinitrochlorobenzene (DNCB) was applied to their dorsal skin on days 1–3. Mice were challenged with DNCB on their ears and dorsal skin on days 14, 17, 20, 23, 26, and 29. BAPD and Dexamethasone were administered to the animals, from days 14–29, and skin severity scores and behavioral tests were determined. Oxidative stress and inflammatory parameters were evaluated on the dorsal skin of mice. Na +, K + -ATPase activity and corticosterone levels were determined in hippocampus/cerebral cortex and plasma of mice, respectively. BAPD improved cutaneous damage, scratching behavior, inflammatory and oxidative stress markers. BAPD showed anxiolytic- and antidepressant-like effects and restored Na +, K + -ATPase activity and corticosterone levels. The present study was performed using female mice due the susceptibility for this disease. But, the evaluation of AD model in male mice would help to verify whether the male gender has the same predisposition to present this pathology. Our data demonstrated the suppressive effect of BAPD on psychiatric disorders – AD comorbidity by regulating inflammatory and oxidative status in mice. Graphical abstract: Image 1 Highlights: BAPD attenuated DNCB-induced AD, depressive and anxious symptoms in mice. The treatment with BAPD improved inflammatory parameters in an AD model. The oxidative stress induced by DNCB was reduced by BAPD. The efficacy of BAPD was similar or superior to Dexamethasone.